Biotechnological production of polyphosphate from industrial wash water. Issue 2 (8th November 2022) - Fees, Jana; Christ, Jonas J.; Willbold, Sabine; Blank, Lars M.
Abstract: Phosphate is mined from phosphate rock, which is a limited resource on a human time scale. For a sustainable phosphate supply, strategies for efficient use and recycling of phosphate must be developed. A German chemical company produces annually wash water containing phosphate and other inorganic substances (e.g., sodium, potassium, sulfate, and chloride) at a ton scale. Chemical precipitation is mostly used for phosphate removal. In this study, a biotechnological process utilizing Saccharomyces cerevisiae to upcycle phosphate‐containing wastewater into pure sodium polyphosphate in powder form was developed. The process comprises fermentation and downstream processing (polyphosphate yields: 25% and 36%, respectively). The polyphosphate quality was independent of the wash water composition. Polyphosphate with a purity of 23% molar ratio Na to Na, K, and Mg of > 90%, and with an average chain length of 12.5 phosphate subunits was produced. The upcycled polyphosphate can be reused compared to phosphate fertilizer in many different applications. Overall, the here developed process can contribute to truly slowing down phosphate mining and finally enable a sustainable utilization of phosphate. Thereby, the benefit of the process is the cascade use of phosphate, reducing the need for phosphate rock before the phosphate ends up in the soil and ultimately in the sea. Abstract : The biotechnological production of pure sodium polyphosphate by Saccharomyces cerevisiae utilizing phosphate‐containing industrial wash water is described. The authors compared the polyphosphate production with different phosphate‐rich wash waters and were able to show that the polyphosphate quality was independent of the wash water composition.